Killing Spanish - Sandin, L. author. aut Link
X, 167 p.
Keywords: In this intelligent monograph for women's studies, literature and Latin American studies, Lyn Di Iorio Sandin asserts that there is a significant ambivalence surrounding identity that is present in the works of Latino writers such as Cristina Garcia, Edward Rivera, and Abraham Rodriguez. Sandin incorporates the theories of allegory and 'double identity' to talk about fragmentation of the Latino psyche. What Sandin finds compelling is that in all of the works of this diverse group of writers, there is a common theme of anxiety about origins that manifests itself through the symbols of dead women, ghosts, or madwomen. Using specific examples from literature ranging from Cuban American Cristina Garcia's The Aguero Sisters to Puerto Rican Rosario Ferre's Maldito amor , Sandin finds that fragmented ethnic identification is an area that is just beginning to be explored within the analysis of U.S. Latino fiction.